2008
DOI: 10.1002/art.24024
|View full text |Cite
|
Sign up to set email alerts
|

Severity of baseline magnetic resonance imaging–evident sacroiliitis and HLA–B27 status in early inflammatory back pain predict radiographically evident ankylosing spondylitis at eight years

Abstract: Objective. Magnetic resonance imaging (MRI) is increasingly used to detect sacroiliitis earlier. This study was undertaken to investigate what proportion of patients with MRI-evident sacroiliitis develop ankylosing spondylitis (AS) in the long term and whether there are predictors of outcome.Methods. Consecutive undiagnosed patients with early inflammatory back pain (IBP) (of <2 years' duration) were assessed clinically and radiologically. Baseline imaging assessments included fat-suppressed MRI sequences of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
177
2
17

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 335 publications
(209 citation statements)
references
References 12 publications
7
177
2
17
Order By: Relevance
“…This requirement is challenging in the early stages of the disease because structural changes on pelvic radiographs, which constitute the basis of the modified New York criteria for classifying SpA, may take Ͼ10 years to become apparent (6,7). Consequently, the expert opinion of clinicians has been used as a gold standard, which has obvious limitations associated with false-positive or false-negative assignments and ultimately still requires a lengthy followup period to ascertain the development of radiographic sacroiliitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This requirement is challenging in the early stages of the disease because structural changes on pelvic radiographs, which constitute the basis of the modified New York criteria for classifying SpA, may take Ͼ10 years to become apparent (6,7). Consequently, the expert opinion of clinicians has been used as a gold standard, which has obvious limitations associated with false-positive or false-negative assignments and ultimately still requires a lengthy followup period to ascertain the development of radiographic sacroiliitis.…”
Section: Introductionmentioning
confidence: 99%
“…Two interventional trials of nr-axSpA reported a symptom duration of 7-8 years and 10.1 years with HLA-B27 frequencies of 59 -75% and 70 -75%, respectively (22,23). In 2 prospective studies of SpA inception cohorts with 7.7 and 10 years of followup, only 33.3% and 24.3% of nr-axSpA patients, respectively, progressed to radiographic sacroiliitis, meeting the modified New York criteria (7,24). …”
mentioning
confidence: 99%
“…This is principally because the diagnostic radiographic changes in the SI joints and spine usually develop slowly (1). Fat-suppressed MRI enables identification of osteitis at disease presentation and has the potential to transform the diagnosis of axial SpA, since much of the axial pathology is related to a diffuse perifibrocartilage osteitis, either in the SI joints or at the entheses in the spine (2)(3)(4).…”
mentioning
confidence: 99%
“…It is generally assumed that these MRI patterns of disease can be used to distinguish SpA from other diseases. Indeed, these lesions are being used to diagnose axial SpA early in its onset (3,8) and might influence early initiation of biologic therapy; for this purpose, several systems of scoring spinal BME lesions have been established (6,(9)(10)(11)(12). However, the specificity of these spinal BME lesions for SpA and their diagnostic utility for SpA have not been confirmed.…”
mentioning
confidence: 99%
“…Furthermore, recent work has confirmed the predictive value of an abnormal MRI in a group of patients with early inflammatory back pain. The combination of severe BMO lesions (according to the Leeds MRI Scoring System) and a positive HLA B27 each gave a sensitivity and specificity of 77 % for the subsequent development of radiographic sacroiliitis [3]. These findings were confirmed in a separate prospective study.…”
Section: Mri In the Diagnosis And Classification Of Asmentioning
confidence: 56%